Step (1): Assume given statement
Let the given statement be P(n), i.e.,
P(n):1+1(1+2)+1(1+2+3)+⋯+1(1+2+3+⋯+n)=2nn+1
Step (2): Checking statement P(n) for n=1
Put n=1 in P(n), we get
P(1):1=2×11+1
=22=1
⇒1=1
Thus P(n) is true for n=1
Step (3): P(n) for n=K
Put n=K in P(n) and assume this is true for some natural number K i.e.,
P(K):1+1(1+2)+1(1+2+3)+⋯+1(1+2+⋯+K)=2KK+1 ⋯(1)
Step (4): Checking statement P(n) for n=K+1
Now we shall prove that P(K+1) is true whenever P(K) is true.
Now, we have
1+1(1+2)+1(1+2+3)+⋯+1(1+2+...+K)+1(1+2+⋯+(K+1))
=2KK+1+1(1+2+3+⋯+(K+1)) (Using (1))
∵ We know that
1+2+3+⋯+n=n(n+1)2
So, we get
=2KK+1+1(K+1)(K+1+1)2
=2KK+1+2(K+1)(K+2)
=2k(K+1)+2(K+1)(K+2)
=2(K+1)(K+2)[K2+2K+1]
=2(K+1)2(K+1)(K+2)
= 2(K+1)(K+2)
We can write it as, =2(K+1)[(K+1)+1]
Thus, P(K+1) is true whenever P(K) is true.
Final Answer.
Hence, from the principle of mathematical induction, the statement P(n) is true for all n∈N.